1984
DOI: 10.1063/1.1137806
|View full text |Cite
|
Sign up to set email alerts
|

Note on the design of simple indium O-ring seals

Abstract: Various different applications of indium O-ring seals are briefly reviewed. A critical factor in the construction of any indium pressure-type seal is the finish of the surface cold welding to the indium. We present the results of some tests on surface finishes achieved by machining and grinding, which indicate certain conditions which ensure the integrity of the seal. Specifically, we find that if the metal surface has to be ground, it should be ground, and then polished to a surface granularity of less than 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The term "glass" here is meant in a broader sense to refer to optically transparent materials and includes quartz, vitreous silica, sapphire, and similar materials. The main advances in the field of metalto-glass joints that are hydrogen and helium-tight, have been made in the 1950s-1960s [21][22][23][24][25] , among others to seal a large liquid hydrogen bubble chamber 26 , and in the 1980s [27][28][29][30] . A substantial overview of published indium seal designs was given by Turkington and Harris-Lowe 28 .…”
Section: Indium Sealmentioning
confidence: 99%
See 2 more Smart Citations
“…The term "glass" here is meant in a broader sense to refer to optically transparent materials and includes quartz, vitreous silica, sapphire, and similar materials. The main advances in the field of metalto-glass joints that are hydrogen and helium-tight, have been made in the 1950s-1960s [21][22][23][24][25] , among others to seal a large liquid hydrogen bubble chamber 26 , and in the 1980s [27][28][29][30] . A substantial overview of published indium seal designs was given by Turkington and Harris-Lowe 28 .…”
Section: Indium Sealmentioning
confidence: 99%
“…The main advances in the field of metalto-glass joints that are hydrogen and helium-tight, have been made in the 1950s-1960s [21][22][23][24][25] , among others to seal a large liquid hydrogen bubble chamber 26 , and in the 1980s [27][28][29][30] . A substantial overview of published indium seal designs was given by Turkington and Harris-Lowe 28 . All previous designs that describe metal-to-glass joints use, however, flat glass slabs of appreciable thicknessin the range of several millimeters to centimeters -and of corresponding mechanical strength.…”
Section: Indium Sealmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of design considerations for indium O-ring seals can be found in Turkington and Harris-Lowe. 46 The key steps in the window assembly and installation procedure used here are summarized in Fig. 7.…”
Section: Window Installation On the Receiver And Superfluid-tight Ind...mentioning
confidence: 99%
“…More recently, Döge and Hingerl 45 described the use of a hydrogen-tight cryogenic vacuum seal employing indium wire gaskets for amorphous silica windows. A review of design considerations for indium O-ring seals can be found in Turkington and Harris-Lowe 46 .…”
Section: Window Installation On the Receiver And Superfluid-tight Ind...mentioning
confidence: 99%